Polyimide molding powder and preparation method thereof
By mixing the polyamic acid solution with a hot mixed solvent for thermal imidation, the problems of low heat transfer efficiency caused by direct heating and insufficient decomposition of polyamic acid are solved, and the high molecular weight and excellent thermal stability of the polyimide molding powder are achieved.
Patent Information
- Application Number
- CN202411865546.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
AI Technical Summary
In the existing preparation methods of polyimide molding powder, direct heating leads to low heat transfer efficiency, insufficient decomposition of polyamic acid, and a large amount of small molecule powder are generated, affecting the heat resistance and quality of the product.
The method of mixing the polyamic acid solution with a hot mixed solvent (including the first organic solvent and azeotropic water-belt agent) for thermal imidation is adopted to heat imidize it by rapidly increasing the heat transfer efficiency and reducing the decomposition of the polyamic acid.
It effectively improves the molecular weight and thermal stability of polyimide molding powder, reduces the generation of small-molecular powder, and improves the quality and mechanical properties of the product.
Smart Images

Figure BDA0005196470250000101 
Figure HDA0005196470420000011 
Figure HDA0005196470420000012
Abstract
Description
Technical Field
[0001] The invention relates to polyimide molding powder and a preparation method thereof, and belongs to the field of material synthesis. Background Art
[0002] Polyimide is the earliest industrialized variety of aromatic heterocyclic high temperature resistant polymers and one of the varieties with the best heat resistance among engineering plastics. Polyimide has excellent comprehensive properties, such as good mechanical properties at temperatures between -200 and 260°C, excellent electrical insulation, chemical stability, radiation resistance, and flame retardancy.
[0003] As a special engineering material, polyimide has been widely used in aviation, aerospace, microelectronics, nano, liquid crystal, separation membrane, laser and other fields, and was once hailed as one of the most promising engineering plastics in the 21st century. Polyimide sheets and rods are made of polyimide molding compounds through high temperature and high pressure molding, so the quality of the molding compounds directly affects the product quality and mechanical properties of sheets and rods.
[0004] The preparation of polyimide molding powder in references 1 to 3 is all done by directly heating polyamic acid to dehydrate and imide it. However, these processes are currently limited by the influence of the heat transfer efficiency of the reaction system, resulting in a slow heating rate of the polyamic acid. Before the dehydration temperature is reached, a large amount of high molecular weight polyamic acid is thermally decomposed into low molecular weight polyamic acid, resulting in a large amount of small molecule powder mixed in the molding powder after the reaction is completed. The small molecule powder has poor heat resistance, which causes these small molecule powders to carbonize during the preparation of plates and rods under high temperature and high pressure, resulting in internal defects in the plates and rods, thereby affecting product quality and mechanical properties. In addition, due to the high viscosity of polyamic acid, the heat of the kettle wall cannot be quickly transferred to the kettle when directly heated, resulting in the polyamic acid sticking to the kettle wall being dehydrated and formed into films first. These polyimide films can easily block pipelines in industrial projects, bringing inconvenience to industrial production.
[0005] Reference 3 proposes a method of combining chemical imidization with thermal imidization. However, this method uses a large number of chemical reagents, the subsequent distillation and recovery operations are cumbersome, and the energy consumption and production costs are also high.
[0006] Therefore, it is urgent to obtain high-quality polyimide molding powder through a method that is efficient, convenient, simple in process, and has low equipment requirements.
[0007] References:
[0008] Reference 1: CN101423608A
[0009] Reference 2: CN113292726A
[0010] Reference 3: CN1445260A
[0011] Reference 4: CN1428360A Summary of the invention
[0012] Problem that the invention aims to solve
[0013] In order to solve the problem that a large amount of small molecular powder is produced by directly heating polyamic acid to prepare molding powder in the past, the present invention provides a method for preparing polyimide molding powder with simple process, low equipment requirements, high heat transfer efficiency and the ability to effectively reduce the decomposition of polyamic acid.
[0014] Furthermore, the present invention also provides a polyimide molding powder, which has the characteristics of higher intrinsic viscosity, higher molecular weight and excellent thermal stability compared with the polyimide molding powder prepared by the traditional direct heating method.
[0015] Solutions for solving problems
[0016] The present invention first provides a method for preparing a polyimide molding powder, which comprises the following steps:
[0017] The polyamic acid solution is mixed with a hot mixed solvent to perform thermal imidization to obtain a polyimide molding powder;
[0018] Wherein, the hot mixed solvent comprises a first organic solvent and an azeotropic water-carrying agent;
[0019] The temperature of the hot mixed solvent is 100-160°C.
[0020] According to the preparation method of the present invention, the solid content of the polyamic acid solution is 15%-50%; and / or,
[0021] The weight average molecular weight of the polyamic acid is 100,000 to 300,000 g / mol, and the number average molecular weight of the polyamic acid is 50,000 to 150,000 g / mol.
[0022] According to the preparation method of the present invention, the first organic solvent comprises one or a combination of two or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; and / or,
[0023] The azeotropic water-carrying agent includes one or a combination of two or more of benzene, toluene, xylene and ethylene dichloride.
[0024] According to the preparation method of the present invention, the azeotropic water-carrying agent accounts for 40% to 70% of the total weight of the hot mixed solvent.
[0025] According to the preparation method of the present invention, the polyamic acid solution and the hot mixed solvent are mixed for 0.5h to 3h; and / or,
[0026] The thermal imidization time is 2h to 6h.
[0027] According to the preparation method of the present invention, the preparation method further comprises the step of preparing a polyamic acid solution: mixing an aromatic carboxylic acid dianhydride, a diamine monomer and a second organic solvent to perform a polymerization reaction to obtain the polyamic acid solution;
[0028] Preferably, the aromatic carboxylic acid dianhydride comprises one or a combination of two or more of benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, diphenyl ether tetracarboxylic dianhydride and pyromellitic tetracarboxylic dianhydride; and / or,
[0029] The diamine monomer includes one or a combination of two or more of diaminodiphenyl ether, 1,3-bis(4'-aminophenoxy)benzene, and meta-phenylenediamine.
[0030] According to the preparation method of the present invention, the molar ratio of the aromatic carboxylic acid dianhydride to the diamine monomer is 0.95:1 to 1.1:1; preferably, a capping agent is also added in the step of preparing the polyamic acid solution;
[0031] More preferably, the end-capping agent comprises phthalic anhydride and / or aniline;
[0032] More preferably, the amount of the end-capping agent is 0.05% to 3% of the total mass of the aromatic carboxylic acid dianhydride and the diamine monomer.
[0033] According to the preparation method of the present invention, the second organic solvent comprises one or a combination of two or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; and / or,
[0034] The polymerization reaction temperature is 15° C. to 40° C., and the polymerization reaction time is 1 h to 5 h.
[0035] In addition, the present invention also provides a polyimide molding powder, wherein the polyimide molding powder is prepared by the preparation method of the present invention.
[0036] According to the polyimide molding powder of the present invention, the weight average molecular weight of the polyimide molding powder is 80,000 g / mol or more, preferably 80,000 to 200,000 g / mol; the number average molecular weight of the polyimide molding powder is 35,000 g / mol or more, preferably 35,000 to 100,000 g / mol.
[0037] Effects of the Invention
[0038] The preparation method of the polyimide molding powder provided by the present invention has simple process, low equipment requirements, high heat transfer efficiency, can effectively reduce the decomposition of polyamic acid, has high yield, and has a fast powder discharge speed during the reaction process. The problem of directly heating polyamic acid causing a polyimide film to form on the wall of the reactor and product agglomeration due to uneven heat transfer can be eliminated.
[0039] Compared with the polyimide molding powder obtained by the traditional preparation method, the polyimide molding powder provided by the present invention has higher intrinsic viscosity, higher molecular weight and excellent thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The polyimide molding powder prepared in Example 1 is shown;
[0041] Figure 2 The GPC test result diagram of the polyamic acid prepared in Example 5 is shown;
[0042] Figure 3 The figure shows the GPC test result of the polyimide molding powder prepared in Example 5;
[0043] Figure 4 The GPC test result diagram of the polyamic acid prepared in Example 6 is shown;
[0044] Figure 5 The figure shows the GPC test result of the polyimide molding powder prepared in Example 6;
[0045] Figure 6 The polyimide molding powder prepared in Comparative Example 1 is shown;
[0046] Figure 7 A photo of polyimide agglomerates bonded to the kettle wall produced during the preparation of polyimide molding powder in Comparative Example 3 is shown;
[0047] Figure 8 The GPC test result diagram of the polyamic acid prepared in Comparative Example 5 is shown;
[0048] Fig. 9 The figure shows the GPC test result of the polyimide molding powder prepared in Comparative Example 5;
[0049] Fig.10 The GPC test result diagram of the polyamic acid prepared in Comparative Example 6 is shown;
[0050] Fig.11 The GPC test result graph of the polyimide molding powder prepared in Comparative Example 6 is shown. DETAILED DESCRIPTION
[0051] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0052] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0053] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0054] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0055] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0056] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0057] <First aspect>
[0058] A first aspect of the present invention provides a method for preparing a polyimide molding powder, comprising the following steps:
[0059] The polyamic acid solution is mixed with a hot mixed solvent for thermal imidization to obtain a polyimide molding powder; wherein the hot mixed solvent comprises a first organic solvent and an azeotropic water-carrying agent;
[0060] The temperature of the hot mixed solvent is 100-160°C.
[0061] The present invention heats up and dehydrates a polyamic acid solution by mixing it with a hot mixed solvent, thereby achieving thermal imidization. This can not only improve the heat transfer efficiency, effectively reduce the decomposition of polyamic acid, improve the yield, and increase the molecular weight of polyimide molding powder, thereby improving the heat resistance of the molding powder, but also eliminate the problem of polyimide film being generated on the wall of the reactor due to uneven heat transfer when directly heating the polyamic acid, thereby facilitating industrial production.
[0062] Polyamic acid solution
[0063] In the present invention, the solid content of the polyamic acid solution can be 15% to 50%, preferably 30% to 50%, for example, 20%, 25%, 35%, 40%, 45%, etc.; when the solid content of the polyamic acid solution is lower than 15%, it is not conducive to the polymerization reaction, resulting in a low molecular weight of the obtained polyamic acid, and it is difficult to obtain a high molecular weight polyimide molding powder; when the solid content of the polyamic acid solution is 15% to 50%, the water content in the solvent has little effect on the polymerization reaction, which is conducive to the polymerization reaction, and a polyamic acid with a suitable molecular weight can be obtained.
[0064] The weight average molecular weight of the polyamic acid is 100000-300000 g / mol, for example, 120000 g / mol, 150000 g / mol, 180000 g / mol, 20000 g / mol, 220000 g / mol, 250000 g / mol, 280000 g / mol, etc. The number average molecular weight of the polyamic acid is 50000-150000 g / mol, for example, 70000 g / mol, 90000 g / mol, 100000 g / mol, 110000 g / mol, 130000 g / mol, etc. The intrinsic viscosity of the polyamic acid is 1 dL / g to 5 dL / g, for example, 1.5 dL / g, 2 dL / g, 2.5 dL / g, 3 dL / g, 3.5 dL / g, 4 dL / g, 4.5 dL / g, etc.
[0065] In some specific embodiments, the preparation method of the present invention further comprises the step of preparing a polyamic acid solution: mixing an aromatic carboxylic acid dianhydride, a diamine monomer and a second organic solvent to perform a polymerization reaction to obtain the polyamic acid solution.
[0066] The present invention does not particularly limit the type of the aromatic carboxylic dianhydride, which can be selected as needed, for example, it can include one or a combination of two or more of benzophenonetetracarboxylic dianhydride (BTDA), biphenyltetracarboxylic dianhydride (BPDA), diphenyl ether tetracarboxylic dianhydride (ODPA), pyromellitic dianhydride (PMDA), etc.
[0067] The present invention does not particularly limit the type of the diamine monomer, and it can be selected as needed. For example, it can include one or a combination of two or more of diaminodiphenyl ether (ODA), 1,3-bis(4'-aminophenoxy)benzene (TPER), metaphenylenediamine (MPD), etc.
[0068] The molar ratio of the aromatic carboxylic acid dianhydride to the diamine monomer is not particularly limited in the present invention and can be selected as needed, for example, 0.95:1 to 1.1:1, preferably 1:1 to 1.1:1, for example: 0.97:1, 0.99:1, 1.01:1, 1.03:1, 1.05:1, 1.07:1, 1.09:1, etc. When the molar ratio of the aromatic carboxylic acid dianhydride to the diamine monomer is 0.95:1 to 1.1:1, the desired polyamic acid solution can be prepared. Preferably, the aromatic carboxylic acid dianhydride is selected in excess to promote the reaction, and the aromatic carboxylic acid dianhydride can play a capping role.
[0069] In some specific embodiments, a capping agent may be added in the step of preparing the polyamic acid solution. The present invention does not specifically limit the type of the capping agent, which may include phthalic anhydride and / or aniline. The amount of the capping agent may be 0.05% to 3% of the total mass of the aromatic carboxylic acid dianhydride and the diamine monomer, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, etc.
[0070] The present invention does not specifically limit the type of the second organic solvent, and it can be selected as needed. For example, it can include one or a combination of two or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, etc.
[0071] The polymerization reaction temperature may be 15°C to 40°C, for example, 20°C, 25°C, 30°C, 35°C, etc.; the polymerization reaction time may be 1h to 5h, for example, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, etc.
[0072] In some specific embodiments, the step of preparing the polyamic acid solution can be performed under the protection of nitrogen.
[0073] Hot mixed solvent
[0074] In the present invention, the hot mixed solvent includes a first organic solvent and an azeotropic water-carrying agent.
[0075] The present invention does not specifically limit the type of the first organic solvent, and it can be selected as needed. For example, it can include one or a combination of two or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, etc.
[0076] The type of the azeotropic water-carrying agent may include one or a combination of two or more of benzene, toluene, xylene, ethylene dichloride, etc.
[0077] The dosage of the azeotropic water-carrying agent can be 40% to 70% of the total weight of the hot mixed solvent, for example, it can be 45%, 50%, 55%, 60%, 65%, etc. When the dosage of the azeotropic water-carrying agent is 40% to 70% of the total weight of the hot mixed solvent, the steam amount of the water-carrying agent of the volatile component of the solution can be increased, so that the water generated in the thermal imidization process can be removed as soon as possible, so that the reaction can proceed rapidly and forwardly.
[0078] The temperature of the hot mixed solvent of the present invention is 100°C to 160°C, preferably 120°C to 160°C, for example, 110°C, 120°C, 130°C, 140°C, 150°C, etc. When the temperature of the hot mixed solvent is 100°C to 160°C, the decomposition of polyamic acid can be effectively reduced and the molecular weight of polyimide molding powder can be increased; when the temperature of the hot mixed solvent is lower than 100°C, it is not conducive to the reaction, and when it is below 100°C for a long time, it will cause a large amount of decomposition of polyamic acid; when the temperature of the hot mixed solvent is higher than 160°C, it is easy to cause waste of resources.
[0079] Thermal imidization
[0080] In the present invention, the polyimide molding powder is obtained by mixing the polyamic acid solution and the hot mixed solvent to perform thermal imidization.
[0081] The mixing time of the polyamic acid solution and the hot mixed solvent can be 0.5h to 3h, for example, 1h, 1.5h, 2h, 2.5h, etc. In some specific embodiments of the present invention, the mixing method can be adding the polyamic acid solution to the hot mixed solvent by dropwise addition.
[0082] The time for the thermal imidization can be 2 hours to 6 hours, such as 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, etc. In some specific embodiments of the present invention, the thermal imidization is carried out under heat preservation conditions.
[0083] Additional Steps
[0084] In some specific embodiments of the present invention, in the preparation method of the present invention, a post-treatment step is further included after the thermal imidization, and the post-treatment includes cooling filtration, washing, drying, etc.
[0085] The cooling and filtering step comprises cooling the polyimide molding powder obtained after the thermal imidization to room temperature and filtering. The washing step comprises washing the filtered polyimide molding powder with an organic solvent. There is no particular limitation on the type of the organic solvent, which can be selected as needed, for example, acetone, etc. The drying step comprises drying the washed polyimide molding powder, which can be specifically vacuum drying. Preferably, the drying temperature can be 200°C to 300°C, and the drying time can be 2h to 8h.
[0086] <Second Aspect>
[0087] The second aspect of the present invention provides a polyimide molding powder, which is prepared by the preparation method described in the first aspect of the present invention.
[0088] The thermal imidization method used in the traditional preparation method of polyimide molding powder usually directly heats the reaction. When directly heating the temperature, the heat of the kettle wall cannot be quickly transferred to the kettle, which causes the polyamic acid adhering to the kettle wall to dehydrate and form a film first, and even form agglomerates, such as Figure 7 As shown, these polyimide films and agglomerates will not only easily block pipelines in industrial projects, but also the obtained polyimide molding powder will be doped with foreign films (such as Figure 6 The method provided by the present invention can improve the heat transfer efficiency, so that the polyamic acid solution is quickly heated and dehydrated for thermal imidization, thereby preventing the generation of polyimide film and improving the quality of the product.
[0089] The weight average molecular weight of the polyimide molding powder obtained by the preparation method of the present invention is 80000 g / mol or more, preferably 80000-200000 g / mol, for example, 90000 g / mol, 100000 g / mol, 110000 g / mol, 120000 g / mol, 130000 g / mol, 140000 g / mol, etc. The number average molecular weight of the polyimide molding powder is 35000 g / mol or more, preferably 35000-100000 g / mol, for example, 40000 g / mol, 50000 g / mol, 60000 g / mol, 70000 g / mol, 80000 g / mol, 90000 g / mol, etc. The intrinsic viscosity of the polyimide molding powder is greater than 0.7 dL / g, preferably 0.7 dL / g to 1.5 dL / g, for example, 0.8 dL / g, 0.9 dL / g, 1 dL / g, 1.1 dL / g, 1.2 dL / g, 1.3 dL / g, 1.4 dL / g, etc.
[0090] Compared with the polyimide molding powder obtained by the traditional preparation method, the polyimide molding powder obtained by the preparation method of the present invention has higher intrinsic viscosity and higher molecular weight, and thus has excellent thermal stability.
[0091] Example
[0092] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0093] The detection method of intrinsic viscosity is as follows: weigh 0.1250g of polyamic acid or molding powder, dissolve it in 25mL DMAc or 98% concentrated sulfuric acid, take a certain amount of solution into an Ubbelohde viscometer with an inner diameter of 0.58mm or 1.03mm, put it into a constant temperature water bath at a temperature of 30±0.2℃, measure the outflow time of pure solvent and dissolved sample, record them as t0 and t respectively, and calculate the intrinsic viscosity according to the following formula.
[0094]
[0095] Where, t is the outflow time of the sample solution in the capillary, s;
[0096] t0—the elution time of pure solvent in the capillary, s;
[0097] c—grams of sample dissolved in 100mL of solution, g / dL.
[0098] Example 1
[0099] In one of the 5L glass reactors, 200.24g of diaminodiphenyl ether (ODA) was dissolved in 1500g of dimethylacetamide (DMAc). After stirring and dissolving, 218.12g of pyromellitic dianhydride (PMDA) was added in batches at about 20°C. After reacting for 2h, 4.18g of phthalic anhydride was added. After stirring for another 2h, a polyamic acid solution with a solid content of 21.98% was obtained. At this time, the intrinsic viscosity of the polyamic acid was 2.13dL / g.
[0100] In another 5L glass reactor, add 842.5g of dimethylacetamide and 865g of xylene, and heat the mixed solvent in the reactor to 140°C. The prepared polyamic acid solution is transported into the reactor by a screw pump for about 1 hour. After the transport is completed, continue to keep warm for 4 hours, then cool and filter, wash with acetone, and finally dry in a vacuum oven at 250°C for 4 hours to obtain a high molecular weight polyimide molding powder. At this time, the intrinsic viscosity of the polyimide molding powder is measured to be 0.91dL / g.
[0101] The polyimide molding powder obtained by the method of Example 1 is as follows Figure 1 As shown by Figure 1 It can be seen that the polyimide molding powder prepared in Example 1 has less impurities and is fine and uniform, has a lighter color, and has a larger molecular weight.
[0102] Example 2
[0103] In one of the 5L glass reactors, 200.24g of diaminodiphenyl ether (ODA) was dissolved in 1500g of N-methylpyrrolidone. After stirring and dissolving, 310.21g of diphenyl ether tetracarboxylic dianhydride (ODPA) was added in batches at about 20°C. After reacting for 2h, 2.55g of aniline was added. After stirring for another 2h, a polyamic acid solution with a solid content of 25.48% was obtained. At this time, the intrinsic viscosity of the polyamic acid was 1.93dL / g.
[0104] In another 5L glass reactor, add 800g N-methylpyrrolidone and 900g toluene, and heat the mixed solvent in the reactor to 130°C. Use a screw pump to transport the prepared polyamic acid solution into the reactor. The material transportation time is about 2h. After the transportation is completed, continue to keep the temperature for 3h, then cool and filter, wash with acetone, and finally dry in a vacuum oven at 210°C for 4h to obtain a high molecular weight polyimide molding powder. At this time, the intrinsic viscosity of the polyimide molding powder is 1.28dL / g.
[0105] Example 3
[0106] In one of the 5L glass reactors, 20.02g of diaminodiphenyl ether (ODA) and 263.09g of 1,3-bis(4'-aminophenoxy)benzene (TPER) were dissolved in 1500g of dimethylformamide. After stirring and dissolving, 310.01g of biphenyltetracarboxylic dianhydride (BPDA) was added in batches at about 20°C. After reacting for 2h, 3g of phthalic anhydride was added. After stirring for another 2h, a polyamic acid solution with a solid content of 28.44% was obtained. At this time, the intrinsic viscosity of the polyamic acid was 2.03dL / g.
[0107] In another 5L glass reactor, add 800g of dimethylformamide and 900g of xylene, and heat the mixed solvent in the reactor to 140°C. Use a screw pump to deliver the prepared polyamic acid solution to the reactor for about 1 hour. After delivery, continue to keep warm for 4 hours, then cool and filter, wash with acetone, and finally dry in a vacuum oven at 250°C for 4 hours to obtain a high molecular weight polyimide molding powder. At this time, the intrinsic viscosity of the polyimide molding powder is 0.88dL / g.
[0108] Example 4
[0109] In one of the 5L glass reactors, 108.14g of m-phenylenediamine (MPD) was dissolved in 1500g of dimethyl sulfoxide. After stirring and dissolving, 322.22g of benzophenonetetracarboxylic dianhydride (BTDA) was added in batches at about 20°C. After reacting for 2h, 2g of phthalic anhydride was added. After stirring for another 2h, a polyamic acid solution with a solid content of 22.37% was obtained. At this time, the intrinsic viscosity of the polyamic acid was 1.95dL / g.
[0110] In another 5L glass reactor, add 800g of dimethyl sulfoxide and 1000g of xylene, and heat the mixed solvent in the reactor to 150°C. Use a screw pump to transport the prepared polyamic acid solution into the reactor. The material transportation time is about 2h. After the transportation is completed, continue to keep the temperature for 4h, then cool and filter, wash with acetone, and finally dry in a vacuum oven at 250°C for 4h to obtain a high molecular weight polyimide molding powder. At this time, the intrinsic viscosity of the polyimide molding powder is 0.78dL / g.
[0111] Example 5
[0112] In one of the 5L glass reactors, 200.24g of diaminodiphenyl ether (ODA) was dissolved in 900g of dimethylacetamide (DMAc). After stirring and dissolving, 218.12g of pyromellitic anhydride (PMDA) was added in batches at about 20°C. After stirring for 2h, a polyamic acid solution with a solid content of 31.73% was obtained. The obtained polyamic acid solution was subjected to GPC detection. The results are as follows: Figure 2 As shown in Table 1, the GPC test results show that the weight average molecular weight of the obtained polyamic acid is 267509 g / mol.
[0113] In another 5L glass reactor, add 800g of dimethylacetamide and 900g of xylene, set the heating oil temperature to 170°C, and first heat the mixed solvent in the reactor to about 142°C. Then use a screw pump to transport the prepared polyamic acid solution into the reactor. The material transportation time is about 1 hour. After the transportation is completed, continue to keep the reaction warm for 4 hours, then cool and filter, wash with acetone, and finally dry in a vacuum oven at 250°C for 4 hours to obtain polyimide molding powder. The obtained polyimide molding powder was subjected to GPC testing, and the results are as follows: Figure 3 As shown in Table 2, the GPC test results show that the weight average molecular weight of the obtained polyimide molding powder is 119478 g / mol.
[0114] Table 1 GPC test results of polyamic acid
[0115] peak Peak area ratio (%) Mn(g / mol) Mw(g / mol) Mw / Mn 1 98.833 115908 267509 2.308 2 1.167 1103 1159 1.051
[0116] Table 2 GPC test results of polyimide molding powder
[0117] peak Peak area ratio (%) Mn(g / mol) Mw(g / mol) Mw / Mn 1 99.025 59135 119478 2.020 2 0.975 1139 1180 1.036
[0118] Example 6
[0119] In one of the 5L glass reactors, 20.02g of diaminodiphenyl ether (ODA) and 263.09g of 1,3-bis(4'-aminophenoxy)benzene (TPER) were dissolved in 900g of dimethylformamide. After stirring and dissolving, 310.01g of biphenyltetracarboxylic dianhydride (BPDA) was added in batches at about 20°C. After stirring for 2h, a polyamic acid solution with a solid content of 39.72% was obtained. The obtained polyamic acid solution was subjected to GPC detection, and the results were as follows: Figure 4 As shown in Table 3, the GPC test results show that the weight average molecular weight of the obtained polyamic acid is 149776 g / mol.
[0120] In another 5L glass reactor, add 800g of dimethylformamide and 900g of xylene, set the heating oil temperature to 170°C, and first heat the mixed solvent in the reactor to about 145°C. Then, use a screw pump to transport the prepared polyamic acid solution into the reactor. The material transportation time is about 1 hour. After the transportation is completed, continue to keep warm for 3 hours, then cool and filter, wash with acetone, and finally dry in a vacuum oven at 250°C for 4 hours to obtain polyimide molding powder. The obtained polyimide molding powder was subjected to GPC testing, and the results are as follows: Figure 5 As shown in Table 4, the GPC test results show that the weight average molecular weight of the obtained polyimide molding powder is 96613 g / mol.
[0121] Table 3 GPC test results of polyamic acid
[0122] peak Peak area ratio (%) Mn(g / mol) Mw(g / mol) Mw / Mn 1 95.541 71887 149776 2.083 2 1.445 1153 1198 1.039 3 3.014 383 460 1.199
[0123] Table 4 GPC test results of polyimide molding powder
[0124] peak Peak area ratio (%) Mn(g / mol) Mw(g / mol) Mw / Mn 1 95.404 39927 96613 2.420 2 2.053 1165 1227 1.053 3 2.543 352 440 1.249
[0125] Comparative Example 1
[0126] In a 5L glass reactor, 200.24g of diaminodiphenyl ether (ODA) was dissolved in 1500g of dimethylacetamide (DMAc). After stirring and dissolving, 218.12g of pyromellitic dianhydride (PMDA) was added in batches at about 20°C. After reacting for 2h, 4.18g of phthalic anhydride was added. After stirring for 2h, a polyamic acid solution with a solid content of 21.98% was obtained. At this time, the intrinsic viscosity of the polyamic acid was 2.13dL / g.
[0127] Subsequently, 842.5 g of dimethylacetamide and 865 g of xylene were added to the polyamic acid solution, and then the temperature in the reactor was raised to 140° C. and kept for 4 hours. After the reaction was completed, the mixture was cooled and filtered, washed with acetone, and finally dried in a vacuum oven at 250° C. for 4 hours to obtain polyimide molding powder. The obtained polyimide molding powder had an intrinsic viscosity of 0.70 dL / g.
[0128] The polyimide molding powder prepared in Comparative Example 1 is as follows Figure 6 As shown. Figure 6 It can be seen that the polyimide molding powder obtained in Comparative Example 1 contains a large amount of polyimide film mixed therein, and the product of Comparative Example 1 has a darker color, a lower molecular weight, and a poorer quality. Figure 1 and Figure 6 It can be seen from the comparison that the polyimide molding powder prepared in Example 1 has higher quality.
[0129] Comparative Example 2
[0130] The polyimide molding powder was prepared by using the raw material ratio of Example 2 and the preparation method described in Comparative Example 1. The intrinsic viscosity of the obtained polyimide molding powder was 0.95 dL / g.
[0131] Comparative Example 3
[0132] The polyimide molding powder was prepared by using the raw material ratio of Example 3 and the preparation method described in Comparative Example 1. The intrinsic viscosity of the obtained polyimide molding powder was 0.72 dL / g.
[0133] In Comparative Example 3, during the process of preparing molding powder by heating polyamic acid, lumps were generated on the kettle wall. The lumps are shown in the attached Figure 7However, no agglomeration was observed in the preparation method of Example 3. It can be seen that the preparation method provided by the present invention solves the problem of easy agglomeration in the traditional heating process.
[0134] Comparative Example 4
[0135] The polyimide molding powder was prepared by using the raw material ratio of Example 4 and the preparation method described in Comparative Example 1. The intrinsic viscosity of the obtained polyimide molding powder was 0.69 dL / g.
[0136] Comparative Example 5
[0137] In a 5L glass reactor, 200.24g of diaminodiphenyl ether (ODA) was first dissolved in 1700g of dimethylacetamide (DMAc) and 900g of xylene. After stirring and dissolving, 218.12g of pyromellitic anhydride (PMDA) was added in batches at about 20°C. After stirring for 2h, a polyamic acid solution with a solid content of 13.86% was obtained. The obtained polyamic acid solution was subjected to GPC detection, and the results were as follows: Figure 8 As shown in Table 5, the GPC test results showed that the weight average molecular weight of the obtained polyamic acid was 244711 g / mol.
[0138] The obtained polyamic acid solution was then directly heated to dehydrate, and the heating oil temperature was set at 170°C. The polyamic acid in the reactor was heated from room temperature to about 142°C for dehydration reaction, and the reaction was kept warm for 4 hours. After the reaction, it was cooled and filtered, washed with acetone, and finally dried in a vacuum oven at 250°C for 4 hours to obtain polyimide molding powder. The obtained polyimide molding powder was subjected to GPC detection. The results are as follows: Fig. 9 As shown in Table 6, the GPC test results show that the weight average molecular weight of the obtained polyimide molding powder is only 78895 g / mol. It can be seen that the weight average molecular weight of the polyimide molding powder prepared by the method of Comparative Example 5 is much lower than that of Example 5.
[0139] Table 5 GPC test results of polyamic acid
[0140] peak Peak area ratio (%) Mn(g / mol) Mw(g / mol) Mw / Mn 1 99.011 104040 244711 2.352 2 0.989 1126 1169 1.038
[0141] Table 6 GPC test results of polyimide molding powder
[0142] peak Peak area ratio (%) Mn(g / mol) Mw(g / mol) Mw / Mn 1 96.090 33324 78895 2.367 2 2.140 1192 1254 1.052 3 1.770 390 461 1.182
[0143] Comparative Example 6
[0144] In a 5L glass reactor, 20.02g of diaminodiphenyl ether (ODA) and 263.09g of 1,3-bis(4'-aminophenoxy)benzene (TPER) were dissolved in 1700g of dimethylformamide and 900g of xylene. After stirring and dissolving, 310.01g of biphenyltetracarboxylic dianhydride (BPDA) was added in batches at about 20°C. After stirring for 2h, a polyamic acid solution with a solid content of 18.57% was obtained. The obtained polyamic acid solution was subjected to GPC detection, and the results were as follows: Fig.10 As shown in Table 7, the GPC test results showed that the weight average molecular weight of the obtained polyamic acid was 144368 g / mol.
[0145] The obtained polyamic acid solution was then directly heated to dehydrate, and the heating oil temperature was set at 170°C. The polyamic acid in the reactor was heated from room temperature to about 145°C for dehydration reaction, and the reaction was kept warm for 3 hours. After the reaction, it was cooled and filtered, washed with acetone, and finally dried in a vacuum oven at 250°C for 4 hours to obtain polyimide molding powder. The obtained polyimide molding powder was subjected to GPC detection. The results are as follows: Fig.11 As shown in Table 8, the GPC test results show that the weight average molecular weight of the obtained polyimide molding powder is only 64432 g / mol. It can be seen that the weight average molecular weight of the polyimide molding powder prepared by the method of Comparative Example 6 is much lower than that of Example 6.
[0146] Table 7 GPC test results of polyamic acid
[0147] peak Peak area ratio (%) Mn(g / mol) Mw(g / mol) Mw / Mn 1 95.376 80227 144368 1.799 2 4.624 1172 1215 1.037
[0148] Table 8 GPC test results of polyimide molding powder
[0149] peak Peak area ratio (%) Mn(g / mol) Mw(g / mol) Mw / Mn 1 92.947 28180 64432 2.286 2 2.082 1188 1237 1.042 3 4.971 386 462 1.197
[0150] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0151] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing a polyimide molding powder, characterized in that: The following steps are involved: The polyamic acid solution is mixed with a hot mixed solvent to perform thermal imidization to obtain a polyimide molding powder; Wherein, the hot mixed solvent comprises a first organic solvent and an azeotropic water-carrying agent; The temperature of the hot mixed solvent is 100-160°C.
2. The preparation method according to claim 1, characterized in that: The solid content of the polyamic acid solution is 15%-50%; and / or, The weight average molecular weight of the polyamic acid is 100,000 to 300,000 g / mol, and the number average molecular weight of the polyamic acid is 50,000 to 150,000 g / mol.
3. The preparation method according to claim 1 or 2, characterized in that: The first organic solvent includes one or a combination of two or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; and / or, The azeotropic water-carrying agent includes one or a combination of two or more of benzene, toluene, xylene and ethylene dichloride.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The azeotropic water-carrying agent accounts for 40% to 70% of the total weight of the hot mixed solvent.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The polyamic acid solution and the hot mixed solvent are mixed for 0.5 h to 3 h; and / or, The thermal imidization time is 2h to 6h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method further comprises: The step of preparing the polyamic acid solution is: mixing an aromatic carboxylic acid dianhydride, a diamine monomer and a second organic solvent to perform a polymerization reaction to obtain the polyamic acid solution; Preferably, the aromatic carboxylic acid dianhydride comprises one or a combination of two or more of benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, diphenyl ether tetracarboxylic dianhydride and pyromellitic tetracarboxylic dianhydride; and / or, The diamine monomer includes one or a combination of two or more of diaminodiphenyl ether, 1,3-bis(4'-aminophenoxy)benzene, and meta-phenylenediamine.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the aromatic carboxylic acid dianhydride to the diamine monomer is 0.95:1 to 1.1:1; preferably, a capping agent is also added in the step of preparing the polyamic acid solution; More preferably, the end-capping agent comprises phthalic anhydride and / or aniline; More preferably, the amount of the end-capping agent is 0.05% to 3% of the total mass of the aromatic carboxylic acid dianhydride and the diamine monomer.
8. The preparation method according to any one of claims 6 or 7, characterized in that: The second organic solvent includes one or a combination of two or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; and / or, The polymerization reaction temperature is 15° C. to 40° C., and the polymerization reaction time is 1 h to 5 h.
9. A polyimide molding powder, characterized in that: The polyimide molding powder is prepared by the preparation method according to any one of claims 1 to 8.
10. The polyimide molding powder according to claim 9, characterized in that: The weight average molecular weight of the polyimide molding powder is greater than 80,000 g / mol, preferably 80,000 to 200,000 g / mol; the number average molecular weight of the polyimide molding powder is greater than 35,000 g / mol, preferably 35,000 to 100,000 g / mol.
Citation Information
Patent Citations
Method for preparing thermoplastic polyimide molding powder
CN101423608A
Polyimide molding powder as well as preparation method and application thereof
CN113292726A
Method for preparing polyimide molding powder
CN1428360A
Method for preparing molding powder of polyimide
CN1445260A